Clinical Efficacy and Safety of an Immune Checkpoint Inhibitor in Combination with Regorafenib Therapy as Second-Line Regimen for Patients with Unresectable Hepatocellular Carcinoma - Li J; Jia Y; Shao C; Li Y; Song J (Dove Medical Press, 2023)
Jinpeng Li,1,* Yuntao Jia,1,* Changdong Shao,2,* Yuanming Li,3 Jinlong Song1 1Intervention Ward 1, Shandong Cancer Hospital and Institute, Shandong First Medical University and Shandong Academy of Medical Sciences, Jinan, Shandong, People's Republic of China; 2Qixia Hospital of Traditional Chinese Medicine Hospital, Qixia, Shandong, People's Republic of China; 3Laizhou Hospital of Traditional Chinese Medicine, Laizhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Jinpeng Li, Intervention Ward 1, Shandong Cancer Hospital and Institute, Shandong First Medical University and Shandong Academy of Medical Sciences, Jinan, Shandong, 250117, People's Republic of China, Tel +86 531 67626412, Fax +86 531 67626411, Email Ljpxxx308@126.comPurpose: This study aimed to evaluate the safety and efficacy of a combination of programmed death-1 (PD-1) inhibitor and regorafenib as second-line treatment for advanced hepatocellular carcinoma (HCC).Patients and Methods: We retrospectively analyzed the data of 38 patients with unresectable HCC who were treated with PD-1 inhibitor in combination with regorafenib as a second⁃line therapy as well as the data of 32 patients treated with regorafenib only therapy as a control. The clinical data, previous treatment strategies, follow-up imaging results, and adverse events during follow-ups were recorded. The mRECIST Criteria were used to evaluate the treatment outcome of intrahepatic lesions, and the Kaplan-Meier method was used to evaluate survival time.Results: Up to the last follow-up, the rego-PD-1 group had higher objective response rate (39.5% vs 15.6%, P = 0.028), longer progression-free survival (median 5.9 vs 4.6 months; P = 0.044), and better overall survival (OS) (median 14.5 vs 9.5 months; P = 0.041) than the regorafenib only group. Among the 38 patients in rego-PD-1 group, 1 patient (2.7%) achieved complete response, 14 patients (36.8%) achieved partial response, 14 patients (36.8%) achieved stable disease, and 9 patients (23.7%) achieved progressive disease. Among the 32 patients in regorafenib alone, 5 (15.6%) achieved partial response, 12 (37.5%) achieved stable disease, and 15 (46.9%) achieved progressive disease. Regorafenib alone, Child-Pugh B, and tumors > 3 were independent prognostic factors for poor OS. The difference in the incidence of grade 3/4 adverse events between the two groups was not statistically significant (36.8% vs 28.1%; P = 0.439). Grade ≥ 3 treatment-related adverse events included hypertension and diarrhea.Conclusion: PD-1 inhibitor combined with regorafenib is a promising regimen in treating patients with unresectable HCC owing to its safety and effectiveness as well as low incidence of serious adverse events with its use.Keywords: hepatocellular carcinoma, immune checkpoint inhibitor, regorafenib, anti-PD-1 antibody, second-line treatment, overall survival